Avaliação da transfusão sanguínea em caprinos - Fonseca, Nayanna Brunna da Silva (2016)
This work aimed to evaluate the clinical, hematological, biochemical, hemogasometric, oxidative stress, lipid peroxidation and transfusion reactions of goats submitted to homologous transfusion of fresh whole blood or stored for 15 and 35 days. Eighteen healthy adult male goats were submitted to the induction of anemia and six hours later were transfused with whole blood stored in CPDA-1 bags (Citrate, phosphate, dextrose and adenine) according to the composite experimental group For 6 animals each: G0 (received fresh blood); G15 and G35 (received blood stored for 15 and 35 days, respectively). The transfusion reactions were recorded during the course of the transfusion, whereas clinical, hematological, biochemical, hemogasometric, oxidative stress and lipid peroxidation parameters were assessed by blood sampling at the following moments: before induction of anemia (TC0); 6 hours after phlebotomy and before transfusion (CT scan); 1, 6, 12, 24 and 96 hours after transfusion (T1, T6, T12, T24 and T96, respectively); 8, 16 and 32 days after transfusion (T8d, T16d and T32d, respectively). Samples of blood were also withdrawn from the pockets, prior to transfusion, for the same analyzes. The pockets of blood stored for 15 and 35 days presented more biochemical changes, hemogasometric, oxidative stress and lipid peroxidation than fresh blood bags. However, the hematological parameters were similar to each other. All groups presented transfusion reactions, among which fasciculations and vocalization occurred more frequently. In the hematological analysis, the animals that received fresh blood presented higher globular volume, number of red blood cells and hemoglobin concentration when compared to the animals that received stored blood. As for the biochemical analysis, after the transfusion it was observed an increase of the proteins in the 3 groups; Transient increase of serum glucose in G0 and G35; Elevation of total bilirubin, direct bilirubin, and urea in G15 and G35; In addition, there was elevation of creatine kinase in the 3 groups. The changes observed in the hemogasometric analysis had no clinical significance, as they were within the reference values for the species. As for oxidative stress, the animals that received stored blood presented disorder in their antioxidant system demonstrated by the alteration of the activity of SOD until the T12. In the analysis of lipid peroxidation there was no difference between the groups for the concentration of malondialdehyde. Thus, it can be concluded that transfusion of fresh total homologous blood was more efficient in restoring blood volume, number of erythrocytes and hemoglobin concentration than the transfusion of stored whole blood. However, transfusion of fresh or stored whole blood did not compromise the blood gas, lipid peroxidation, hepatic and renal functions of goats and proved to be efficient in restoring, among other components, the total proteins. Thus, blood transfusion, as performed in this study, was shown to be safe for use in the clinical practice of this species